A natural tomato slurry as a photosensitizer for dye-sensitized solar cells with TiO2/CuO composite thin films. Issue 2 (22nd January 2019) - Moradiya, Meet A.; Dangodara, Ankita; Pala, Jay; Savaliya, Chirag R.; Dhruv, Davit; Rathod, V.R.; Joshi, Ashwini D.; Shah, N.A.; Pandya, Dhiren; Markna, J.H.
ABSTRACT: We have studied the performance of dye-sensitized solar cells by employing natural dye "anthocyanins" extracted from the tomato slurry as a sensitizer for the TiO2 /CuO photoanode. The extracts were anchored on TiO2 /CuO films deposited on an ITO substrate which was used as a photoanode. The dye adsorbed TiO2 /CuO films electrode, the copper plate as a counter electrode, and iodolyte as an electrolyte were assembled into DSSCs. The conversion efficiency of the DSSCs was found to be 2.96% with a V OC of 0.615 V, J SC of 6.6 mA/cm 2, and an FF of 0.73. This work highlights the use of contribution of the tomato slurry as a natural sensitizer to enhance the efficiency of DSSCs.